The Application of Parabola of safety for Physics Problem Solving - N Hasan (BIOMEJ, 2023)
In this article we calculate the parabola safety and its application for some physics problems. Using equation of motion for projectile we find the Parabola of safety. Deriving the parabola of safety here we used zero descriminant of quadratic equation. Inside parabola safety is unsafe region from projectile.The application of the equation is presented for finding maksimum distance, minimum speed in some cases of problems.